Comparison of Risk Assessment Schemes in GHPs and HACCP, FSMA Preventive Controls for Human Food, ISO 22000, and GFSI Recognized Standards with Risk Scoring Guidance in General Use with Fresh Produce - Suwimol Surareungchai; Chaleeda Borompichaichartkul; Chitsiri Rachtanapun; Nutthachai Pongprasert; Pongphen Jitareerat; Varit Srilaong (Horticulturae, 2022)
The intention of this qualitative research study was to provide a basic risk concept by comparing food risk assessment schemes and preparing general food risk scoring guidance for developing a simple and reliable practical fruit and vegetable qualitative food safety risk matrices for fresh produce entrepreneurs. These practical food safety risk matrices were verified using FDA fruit and vegetable food safety risk data. The FDA data were converted to a qualitative risk matrix referring to the fruit and vegetable 3 × 3 qualitative food safety risk matrix reference model. Other common qualitative risk matrix models, namely 3 × 3, 4 × 3, and 5 × 5, were constructed based on probability and severity scores for each hazard, as given in the FDA data. These were designated as practical fruit and vegetable 3 × 3, 4 × 3, and 5 × 5 qualitative food safety risk matrix models. The results of these models were compared with the fruit and vegetable 3 × 3 reference model. The two best compatible models are the 5 × 5 and 3 × 3 qualitative food safety risk matrix models. A preference test from focus group containing 12 participants showed good satisfaction overall, indicating that the practical fruit and vegetable 3 × 3, 4 × 3, and 5 × 5 qualitative food safety risk matrix models are useful for entrepreneurs. Understanding of basic risk concepts and verified scientific referencing of food safety risk matrices can improve entrepreneur’s risk assessment. This can be performed by using practical–scientific food safety risk matrices.